Use of recycling flows for increasing the conversion and selectivity of reversible consecutive chemical reactions - S. L. Nazanskiy; A. V. Solokhin; O. Yu. Istomina; A. V. Kiyko (Тонкие химические технологии, 2012)
With reversible consecutive reactions as an example the ability of the reactant and side product recycling to achieve high values of conversion and selectivity is studied. Analytical expressions for conversion and selectivity via recycle flow rate are obtained. The numerical simulation confirms the obtained theoretical results.